Threads of suspicion [large type] - Henderson, Dee (Henderson, Dee. Evie Blackwell cold case., 2017)
Detective Evie Blackwell returns with some familiar friends, this time working with a new task force dedicated to solving cold missing-persons cases. She and her new partner, David, have been assigned unrelated cases in Chicago, with Evie searching for a missing college student and David hunting a private investigator who disappeared. In the meantime, personal issues arise for both of them -- David's famous longtime girlfriend may be connected to Evie's case, and Evie is starting to feel pressure to accept her boyfriend's marriage proposal.